2020
DOI: 10.1155/2020/9685482
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MHD Fluids around a Linearly Stretching Sheet in Porous Media with Thermophoresis, Radiation, and Chemical Reaction

Abstract: This paper presents the comparative analysis of MHD boundary layer fluid flow around a linearly stretching surface in the presence of radiative heat flux, heat generation/absorption, thermophoresis velocity, and chemical reaction effects in a permeable surface. The governing equations are highly nonlinear PDEs which are converted into coupled ODEs with the help of dimensionless variables and solved by using semianalytical techniques. The numerical and graphical outcomes are observed and presented via tables an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 35 publications
(44 reference statements)
0
24
0
Order By: Relevance
“…Much advancement is observed in research related to MHD flows over a stretching surface in the literature. Jabeen et al [18] considered a porous surface to study the effects of MHD boundary layer flow over a stretching surface and observed that Maxwell fluid has a high thermal conductivity rate compared to other non-Newtonian fluid models. Rasool et al [19] analyzed the high impact of Darcy medium (porous medium) on MHD nanofluid bounded by a stretching (non-linear) surface.…”
Section: Introductionmentioning
confidence: 99%
“…Much advancement is observed in research related to MHD flows over a stretching surface in the literature. Jabeen et al [18] considered a porous surface to study the effects of MHD boundary layer flow over a stretching surface and observed that Maxwell fluid has a high thermal conductivity rate compared to other non-Newtonian fluid models. Rasool et al [19] analyzed the high impact of Darcy medium (porous medium) on MHD nanofluid bounded by a stretching (non-linear) surface.…”
Section: Introductionmentioning
confidence: 99%
“…e temperature variation within the flow is supposed to be small enough so T 4 can be taken as a linear function of temperature neglecting the higher order term while expanding T 4 in Taylor-series about T ∞ is obtained as [20,21]…”
Section: Formulation Of Flow Modelmentioning
confidence: 99%
“…Also, he concluded that the We and n retard the velocity of fluid but enhance the temperature profile. He declared that DTM is more powerful technique [20,21]. Due to vast number of applications in the industrial, technological, and engineering developments, the Carreau model was further worked out by numerous researchers/authors in the last decades [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Also, he concluded that the We and n retard the velocity of fluid but enhance the temperature profile. He declared that DTM is more powerful technique [34,35]. In the study [36], Arain et al studied the flow behavior of Carreau fluid along rotating circular plates with gyrotactic microorganisms under the effects of magnetic generalized Reynolds # and concluded that fluid viscosity declines in shear thinning case when comparing with Newtonian and shear thickening fluids.…”
Section: Introductionmentioning
confidence: 99%